Diagnosis and treatment of odontomas: A retrospective study of 53 cases - LIU Xianguang; WANG Hanxi; ZHENG Mingxue; WANG Xuxia (Kouqiang hemian waike zazhi)
[Objective:] To summarize the clinical, pathological, diagnosis and treatment characteristics of odontomas. [Methods:] The age, gender, clinical symptoms, imaging manifestations, treatment, and prognosis of 53 patients with odontomas were analyzed retrospectively. [Results:] Among the 53 patients with odontomas, the male∶female ratio was 1.12∶1. 79.2% (42/53) of odontomas were found before the age of 18. Most odontomas patients were asymptomatic, accounting for 60.4% (32/53); followed by local jaw protrusion, accounting for 30.2% (16/53); swelling, pain and swelling discomfort, accounting for 9.4% (5/53). The proportion of impacted teeth caused by odontomas was high, reaching 81.1% (43/53); 7.5% (4/53) of the cases had resorption of adjacent permanent teeth. 81.1% (43/53) of the cases had a clear gap between the odontoma and normal bone tissue boundary, and 18.9% (10/53) of odontomas had ill‐defined or partially ill‐defined borders with normal tissue. There were 45 cases of compound odontoma, accounting for 84.9%, and 8 cases of complex odontoma, accounting for 15.1%. There were embedded teeth in the root of 43 cases, among which 22 cases extracted their teeth because they could not be retained; in 12 cases, the teeth erupted spontaneously; and 9 cases (9/43) achieved the ideal position by orthodontic traction. [Conclusion:] Odontoma is an odontogenic tumor formed by odontogenic tissue. Usually, an accurate diagnosis can be obtained with the help of imaging findings. Odontomas can cause tooth displacement, root resorption, tooth eruption resistance, etc. The effect of surgical removal is good and it is not easy to relapse.